PENGARUH GOOD GOVERNANCE, STANDAR AKUNTANSI PEMERINTAHAN DAN SISTEM PENGENDALIAN INTERN TERHADAP AKUNTABILITAS KEUANGAN DENGAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI (Studi Empiris Pada Organisasi Perangkat Daerah Kabupaten Siak) - Umi Salamah; Kamaliah Kamaliah; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of good governance, government accounting standards and internal control systems to financial accountability with organizational commitment as a moderator. The population in this study is the financial section of the regional apparaturs organization (OPD) Siak Regency as many as 26 OPD and taken 3 respondents. The questionnaire distributed to 78 respondents, and successfully collected again with complete answers obtained from taken by the method of purposive sampling. Each of the population represented 3 respondents namely head of finance, treasurer, and finance staff. The questionnaires were distributed to respondents, and were collected again with complete answers obtained from 87 respondents. Methods of data analysis used in the study This is a moderate multiple regression with the help of SPSS 21.00 software. The results of partial and simultaneous research indicate that good governance, government accounting standards and internal control system significantly influence financial accountability. So also good governance, government accounting standards and internal control system significant effect on financial accountability moderated by organizational commitment have significant effect with significant level <0,05. Regression analysis yields coefficient of determination (R2) square equal to 0,518 meaning 51,8% variation of dependent variable can be explained by variation of independent variable independent variable in this research able to influence dependent variable, While the rest equal to 48,2% influenced by other variable which not Included in this study.Keywords: good governance, government accounting standards, internal control system, organizational commitment